Pengaruh Proporsi Wortel (Daucus Carota) dan Bunga Melati (Jasmine) Terhadap Sifat Organoleptik Lulur Tradisional - Megasari, Dindy Sinta Megasari; Wilujeng, Biyan Yesi; Munnifah, Siti (Universitas Negeri Surabaya, 2019)
Traditional body scrub is a beneficial body care cosmetic preparation to clean the skin, remove dead skin cells, smooth skin, brighten skin and also provide skin nutrition, relax the body, improve and stimulate blood circulation to the body. This study aims to determine the effect of the carrots and jasmine flour proportion on the organoleptic properties of traditional body scrubs. This is an experimental study with the independent variable is the proportion of carrot and jasmine flour, while the dependent variable is the organoleptic nature which includes color, scent, texture, stickiness and panelist preferences.Data collection using observational form that include 30 participants. Data analysis using single variant analysis and and Duncan's continued test with SPSS version 16. Study results showed that the X2 product with a proportion of 10gr carrot flour, 5gr jasmine flour and 10 grams of rice flour was the best traditional body scrub product with cream color, scent of jasmine, quite rough texture and quite sticky when applied to body criteria. There is an interaction effect of the proportion of carrot flour and jasmine flour on traditional body scrub organoleptic properties which include color, aroma, texture and adhesion.Keywords : traditional body scrub, jasmine, carrot flour, organoleptic.